FOMO AND MENTAL HEALTH EFFECTS OF TIKTOK ON GEN Z - Nur Choiro Siregar (Acceleration: Multidisciplinary Research Journal, 2025)
Media convergence has transformed communication patterns and intensified social media engagement among Generation Z (born 1997–2012). This group’s constant connectivity increases their vulnerability to psychological pressure, particularly the fear of missing out (FOMO). This study aims to analyze how TikTok, as a dominant product of media convergence, contributes to the emergence and intensification of FOMO among adolescents. The research employed a descriptive qualitative method, involving semi-structured interviews with 12 Generation Z participants and non-participant observation of TikTok usage patterns over a four-week period. The data were analyzed using thematic analysis to identify recurring behavioral and psychological indicators of FOMO. The findings show that TikTok’s algorithmic content flow, rapid trend cycles, and participatory culture significantly trigger FOMO, compelling individuals to frequently check updates, follow trends, and compare themselves with peers. Participants experiencing high FOMO also reported lower life satisfaction, increased anxiety, and difficulties maintaining emotional stability. These conditions were found to hinder aspects of adolescent development, particularly identity formation and autonomy. The study concludes that FOMO represents a critical psychosocial impact of media convergence and underscores the need for digital literacy and mental-health-oriented interventions to help Generation Z navigate online environments more healthily.